Open diameter maps on suspensions - Abobaker, Hussam; Roe, Robert (Topology Proceedings, 2023)
It is shown that if X is a metric continuum, which admits an open diameter map, then the suspension of X, admits an open diameter map. As a corollary, we have that all spheres admit open diameter maps.